Fitness levels and physical activity among class A drug users entering prison - Fischer, J; Butt, C; Dawes, H; Foster, C; Neale, J; Plugge, E; Wheeler, C; Wright, N (2012)
Physical activity could benefit drug users' physiological and mental health. Previous research has suggested that physical activity levels change when drug users enter prison. Methods Twenty-five class A drug users who were new to prison answered physical activity and drug use cross-sectional questionnaires, took a submaximal fitness test and wore a pedometer for 1 week. Results Participants' mean aerobic capacity was estimated as 49 mls O 2/kg/min (±12 SD). Their mean selfreported walking distance outside of prison was 4.67 miles on an average day (±4.14 SD). Pedometer data suggest they walked a mean of 1.8 miles/day in prison. Conclusion Many class A drug users entering prison had high levels of fitness and physical activity before admission, often gained from walking. Walking activity reduced when they entered prison, posing a challenge to maintaining healthy activity levels.